WORKSHOP PENYUSUNAN PROPOSAL PENELITIAN TINDAKAN KELAS BAGI GURU MTs SE POKJA WINDUSARI - Delfiyan Widiyanto; Herpindo, Herpindo; Susanti Malasari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This class action research skill is very suitable to be developed in this new normal era because there are so many classroom problems that occur during online and hybrid learning. This community service program aims to help teachers improve the skills of preparing classroom action research proposals. The implementation method used in this PKM consists of interactive discussions, and practices. The results of this community service program include: improving the skills of teachers in compiling class action research proposals, scientific journal publications, mass media publications, draft class action research proposals, and IPR posters.